THE PHILOSOPHY OF EDUCATION IN THE DEVELOPMENT OF SCIENCE BASED ON LOCAL WISDOM - Rita Afrina; Iskandar; Januar Pandapotan; Haryuni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The philosophy of education plays a fundamental role in shaping the direction of knowledge development, including science that is grounded in the values of local wisdom. Human beings possess the innate capacity to think and continuously strive to enhance their knowledge. Naturally endowed with curiosity, humans constantly seek answers to their questions through the pursuit of knowledge, which in turn brings intellectual satisfaction in accordance with the demands of the times. Knowledge is not only about understanding facts but also about seeking truth through proper scientific inquiry. Learning through well-founded scientific reasoning is one of the ways humans pursue truth. This study aims to examine the essence of the philosophy of education in the development of science based on local wisdom. The surrounding natural environment gives rise to unique forms of local wisdom that serve as potential foundations for scientific development. Science—encompassing physics, chemistry, and biology—relies on scientific methods, logical reasoning, and systematic frameworks. This is where the philosophy of science becomes essential in studying, revealing, and solving scientific problems in human life.Developing science based on local wisdom strengthens national identity, fosters ecological awareness, and cultivates learners who think scientifically while remaining rooted in their cultural heritage. This study discusses the importance of developing science based on local wisdom as a means of preserving natural resources, traditions, and cultural practices within society. Through a literature review approach, this paper explores the relevance between educational philosophy and the integration of local values in science education. The findings reveal that the philosophy of education plays a crucial role in framing the development of science that is not only oriented toward scientific rationality but also upholds moral, cultural, and spiritual values within society.